Phraseological motifs for Distinguishing Between Literary Genres. A Case Study on the Motifs of Verbal and Non-Verbal Communication - Novakova, Iva (Kalbotyra, 2021)
The present paper is based on the assumption that the language of the novel is characterized by a statistically relevant overrepresentation of certain linguistic units (e.g. lexemes, key words, collocations and colligations, Siepmann 2015). First steps towards checking the validity of this hypothesis had been undertaken in pioneering works in the 1990s/2000s (e.g. Stubbs & Barth 2003). These studies were however limited by the small size of their (exclusively English) corpora. The present study explores the role of some patterns (phraseological motifs) in distinguishing French literary subgenres. It also proposes a case study of some motifs related to the verbal (dire avec sourire ‘to say with a smile’) and non-verbal communication (adresser un sourire ‘to send a smile’). Unlike traditional corpus-stylistic analyses, which frequently focus on the style of a single author, our corpus-driven approach identifies lexico-syntactic constructions in literary genres which are automatically extracted from the corpora. The main purpose is to show the relevance of the notion of phraseological motif (Legallois 2012; Longrée & Mellet 2013; Novakova & Siepmann 2020) for the distinction of literary subgenres. Linking form and meaning, these ‘multidimensional units’ fulfil pragmatic as well as discursive functions. The data has been extracted from large French corpora of the PhraseoRom research project https://phraseorom.univ-grenoble-alpes.fr. They are accessible on http://phraseotext.univ-grenoble-alpes.fr/phraseobase/index.html and contain 1000 novels (published from the 1950s to the present), partitioned into six sub-corpora: general literature (GEN), crime fiction (CRIM), romances (ROM), historical novels (HIST), science fiction (SF) and fantasy (FY). The results of our study reveal some unexpected differences between the literary subgenres: e.g. the motif dire d’une voix ‘to say in a voice’ in HIST compared to GEN. In FY, expressions of verbal communication are related to shouting and screaming. Expressions related to the non-verbal communication (prendre dans ses bras ‘to take in one’s arms’) are specific to ROM, where body language is overrepresented. In SF, there is a very limited number of these types of expressions. More generally, the motifs provide the link between the micro level (phraseological recurrences) and the macro level (the fictional script).